Learning through play: the effectiveness of the TGFU learning model as a new way to children's motor skills - Lesmana, Diky; Muhammad, Heryanto Nur; juniarto, Pudji; Ridwan, Mochamad (Universitas Suryakancana, 2025)
The purpose of this study was to determine the effect of the Teaching Games for Understanding (TGFU) model on manipulative movement at SDN Johar Baru 13 Central Jakarta. This approach encourages active involvement, decision making, and understanding of game tactics that directly hone students' motor skills. The research method used was Quasi Experiment with One Group Pre-test–post-test design. The sample in this study was 32 students who were determined through total sampling techniques. The data collection instrument used an observation rubric used to assess the competence of basic manipulative movement skills in the form of initial and final tests accompanied by aspects assessed in the assessment rubric, namely throwing, catching, hitting, dribbling, and kicking. Data were analyzed using descriptive statistics, the Shapiro-Wilk normality test, and the paired sample t-test. The results of the data study showed that the average pre-test score was 7.719 and increased to 9.125 at the time of the post-test. The paired t-test produced a significance value of 0.004 (p <0.05), which indicated that there was a significant effect after treatment was given. Thus, the learning approach using the TGFU model is achieved in improving students' motor skills, especially in students' manipulative movements in elementary schools. This study supports changes in learning strategies that are carried out repetitively and boringly towards more adaptive and flexible learning in PJOK subjects.